The Effectiveness of Handling Cases of Sexual Violence Against Women in the Regional Technical Implementation Unit for the Protection of Women and Children (UPTD PPA) in Makassar City - Wulandari; Firman Umar; Nurharsya Khaer Hanafi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
This study aims to find out (i) the forms of handling cases of sexual violence against women by the UPTD PPA Makassar city, (ii) the inhibiting factors in handling sexual cases against women by the UPTD PPA Makassar city, (iii) the realization of the role of the UPTD PPA Makassar city in overcoming obstacles in Handling cases of sexual violence. This type of research is descriptive with a qualitative approach. It is carried out by reviewing data based on facts aiming to explore data and information sourced from the Regional Technical Implementation Unit of the city of Makassar. The results of this study indicate that: (i) The forms of handling cases of sexual violence against women at the UPTD PPA Makassar city are conducting assessments, case assistance, case management and case termination. (ii) Factors that hinder the handling of cases of sexual violence against women at the UPTD PPA Makassar city are the lack of openness of victims, uncooperative families of victims, limited human resources, especially psychologist counselors and legal advisers and the difficulty of evidence in cases of verbal sexual violence. (iii) Realization of the role played by UPTD PPA Makassar city in overcoming obstacles in handling cases of sexual violence, namely building partnerships with other institutions, improving service quality, optimizing outreach and providing safe house protection for victims.